Regulation and functions of the NLRP3 inflammasome in RNA virus infection - Yue, Zhaoyang; Zhang, Xuelong; Gu, Yu; Liu, Ying; Lan, Lin-Miaoshen; Liu, Yilin; Li, Yongkui; Yang, Ge; Wan, Pin; Chen, Xin (Frontiers in Cellular and Infection Microbiology, 2024)
Virus infection is one of the greatest threats to human life and health. In response to viral infection, the host's innate immune system triggers an antiviral immune response mostly mediated by inflammatory processes. Among the many pathways involved, the nucleotide-binding oligomerization domain (NOD)-like receptor protein 3 (NLRP3) inflammasome has received wide attention in the context of viral infection. The NLRP3 inflammasome is an intracellular sensor composed of three components, including the innate immune receptor NLRP3, adaptor apoptosis-associated speck-like protein containing CARD (ASC), and the cysteine protease caspase-1. After being assembled, the NLRP3 inflammasome can trigger caspase-1 to induce gasdermin D (GSDMD)-dependent pyroptosis, promoting the maturation and secretion of proinflammatory cytokines such as interleukin-1 (IL-1β) and interleukin-18 (IL-18). Recent studies have revealed that a variety of viruses activate or inhibit the NLRP3 inflammasome via viral particles, proteins, and nucleic acids. In this review, we present a variety of regulatory mechanisms and functions of the NLRP3 inflammasome upon RNA viral infection and demonstrate multiple therapeutic strategies that target the NLRP3 inflammasome for anti-inflammatory effects in viral infection.